THE IMPLEMENTATION OF DISTANCE STUDYING TO CREATE “SOFT SKILLS” AMONG SPECIALISTS THAT ARE STUDYING IN ACCORDANCE WITH THE PROGRAM “CIVILMILITARY RELATIONS” - Beryslavska, O.; Dobrovolskyi, V.; Gololobov, V. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2020)
The article is dedicated to the capabilities on introducing modern methods and pedagogical technologies (the technologies of distance studying) including the ones that are used in the course of the training of the Armed Forces of the NATO member countries and which could be adapted to the peculiarities of training cadets (students) in accordance to the program of “Civil military relations”. There’re arguments provided, which favor the implementation of technologies of distance studying in the system of military education which will facilitate the engagement of a larger number of participants to obtain and permanently improve the professional military education; the more operative reaction to changes, that are currently ongoing in the modern world and education; the provision of qualitively new educational services by providing access to informational resources including the ones that are developing “soft skills” as competences which are the most required ones for modern specialists. There’s a presented analyses of the open educational platforms with the aim to identify courses which could be used to develop “soft skills” within the framework of training specialists in accordance to the program “Civil-Military relations. It has been determined that the competences “soft skills” are required in the first place for self-development, they represent the best practices of the system of “life-long study” and most certainly have got to be an element of combined studying which happens to be the most suitable for military education. There have been arguments provided in favor of the fact that an important feature of training specialists in the field of civilmilitary cooperation is the intensification of international cooperation in the field of education with the prominent countries in the world and the appropriate structures of NATO member countries, the intensification of participation of personnel in terms of international exercises , training missions, trainings, educational programs, consultations, internships and other events mainly, within the NATO program “The development of military education” and Ukraine-NATO program with the professional development of civil-personnel of the security and defense sector with the engagement of instructors and teachers who have been deployed with this purpose.